2022
DOI: 10.1007/s00330-022-08619-4
|View full text |Cite|
|
Sign up to set email alerts
|

Computed tomography angiography versus Agatston score for diagnosis of coronary artery disease in patients with stable chest pain: individual patient data meta-analysis of the international COME-CCT Consortium

Abstract: Objectives There is conflicting evidence about the comparative diagnostic accuracy of the Agatston score versus computed tomography angiography (CTA) in patients with suspected obstructive coronary artery disease (CAD). Purpose To determine whether CTA is superior to the Agatston score in the diagnosis of CAD. Methods In total 2452 patients with stable chest pain and a clinical indication for invasive coronary angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…The presence of significant obstructive (epicardial) CAD was defined as a diameter reduction of ≥50% on invasive angiography. In this international study, standard CACS > 400 reportedly had relatively high specificity and positive predictive value with an accuracy of around 70% for the presence of angiographically significant epicardial CAD, which may be in line with our results (i.e., 76%) [22]. In the COME-CCT Consortium study, the prevalence of significant obstructive CAD on invasive angiography in patients with standard CACS of 0, 1-99, 100-399, 400-999, and ≥1000 was 16.8%, 35.6%, 55.5%, 70.4%, and 78.5%, respectively [22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The presence of significant obstructive (epicardial) CAD was defined as a diameter reduction of ≥50% on invasive angiography. In this international study, standard CACS > 400 reportedly had relatively high specificity and positive predictive value with an accuracy of around 70% for the presence of angiographically significant epicardial CAD, which may be in line with our results (i.e., 76%) [22]. In the COME-CCT Consortium study, the prevalence of significant obstructive CAD on invasive angiography in patients with standard CACS of 0, 1-99, 100-399, 400-999, and ≥1000 was 16.8%, 35.6%, 55.5%, 70.4%, and 78.5%, respectively [22].…”
Section: Discussionsupporting
confidence: 91%
“…The ROC curve analysis indicated that the best cut-off value of CACS for CAD was 398 in this study, which was close to the established threshold of 400 [1,11]. In the individual patient data meta-analysis of the international COME-CCT Consortium, a total of 2452 patients from 76 studies who underwent both CACS assessment on CT and invasive coronary angiography were included [22]. The presence of significant obstructive (epicardial) CAD was defined as a diameter reduction of ≥50% on invasive angiography.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In stable chest pain patients and negative CAC score, CTA has better diagnostic accuracy and can provide better prognostic information that includes coronary anatomy, assessing noncalcified plaque, characterization of plaque burden and plaque volume, which makes it a desirable tool to diagnose CAD in patients with chest pain or angina equivalent symptoms. [79][80][81] However, excessive radiation exposure and cost-effectiveness make CTA undesirable as a screening tool among low-risk patients and populations. 14 Table 1 describes the summary of selected studies that examine the role of coronary imaging in the development of atherosclerotic CVD.…”
Section: Coronary Ct Angiographymentioning
confidence: 99%
“…Coronary artery calcium (CAC) accompanies the development of advanced atherosclerosis [24]. Society of cardiovascular computed tomography (SCCT) guidelines recommend considering CAC scans among asymptomatic individuals with a risk of ASCVD.…”
Section: Coronary Artery Calcium Progression and Cadmentioning
confidence: 99%